Characterization of porcine simple sequence repeat variation on a population scale with genome resequencing data - Congcong Liu (Nature Portfolio, 2017)
Abstract Simple sequence repeats (SSRs) are used as polymorphic molecular markers in many species. They contribute very important functional variations in a range of complex traits; however, little is known about the variation of most SSRs in pig populations. Here, using genome resequencing data, we identified ~0.63 million polymorphic SSR loci from more than 100 individuals. Through intensive analysis of this dataset, we found that the SSR motif composition, motif length, total length of alleles and distribution of alleles all contribute to SSR variability. Furthermore, we found that CG-containing SSRs displayed significantly lower polymorphism and higher cross-species conservation. With a rigorous filter procedure, we provided a catalogue of 16,527 high-quality polymorphic SSRs, which displayed reliable results for the analysis of phylogenetic relationships and provided valuable summary statistics for 30 individuals equally selected from eight local Chinese pig breeds, six commercial lean pig breeds and Chinese wild boars. In addition, from the high-quality polymorphic SSR catalogue, we identified four loci with potential loss-of-function alleles. Overall, these analyses provide a valuable catalogue of polymorphic SSRs to the existing pig genetic variation database, and we believe this catalogue could be used for future genome-wide genetic analysis.